Impairment Experiences, Identity and Attitudes Towards Genetic Screening: the Views of People with Spinal Muscular Atrophy. Issue 1 (30th June 2017) - Boardman, Felicity K.; Young, Philip J.; Griffiths, Frances E.
Abstract: Developments in genetics are rapidly changing the capacity and scope of screening practices. However, people with genetic conditions have been under‐represented in the literature exploring their implications. This mixed methods study explores the attitudes of people with Spinal Muscular Atrophy (SMA) towards three different population‐level genetic screening programmes for SMA: pre‐conception, prenatal and newborn screening. Drawing on qualitative interviews ( n = 15) and a survey ( n = 82), this study demonstrates that more severely affected individuals with early‐onset symptoms (Type II SMA), are less likely to support screening and more likely to view SMA positively than those with milder, later onset and/or fluctuating symptoms (Types III/ IV SMA). Indeed, this clinically milder group were more likely to support all forms of screening and view SMA negatively. This paper highlights that screening is a complex issue for people with genetic conditions, and the nature of impairment experiences plays a critical role in shaping attitudes.